APLIKASI UNTUK MENILAI KUALITAS LAYANAN JASA PADA ZHAHIRA LAUNDRY MENERAPKAN DIMENSI SERVQUAL - Pirganta, Ari Tri; Diana, Diana (J-Icon : Jurnal Komputer dan Informatika, 2024)
Zhahira Laundry is a business that provides laundry services. However, the quality of Zhahira Laundry services provided is not always in accordance with consumer expectations, there are obstacles that affect the quality of laundry services. To overcome these problems, Zhahira Laundry requires the Zhahira Laundry Assessment Application (APZAL). An application created to display a web-based questionnaire that will be assessed by customers. In this study, the quality of service that is the main thing in solving problems can be measured by Service Quality (Servqual) which consists of service quality factors such as tangible, dependability, responsibility, assurance and empathy. There is a purpose of measurement based on the Servqual is to determine the value of the gap between expectations and perceptions that occur regarding the services provided through the five dimensions of Servqual tangible, response, dependable, assurance, and empathy. This application can be accessed online by scanning the barcode listed using only Android. This application can identify gaps (GAP) in the Servqual dimension indicators. The GAP value is the result of reducing the scale of very satisfying expectations 5.00 and the service quality score for each Servqual dimension is calculated through ranking in each question indicator based on the GAP value from the highest to the lowest. Based on the GAP value after being implemented and used by customers, what is the GAP and ranking produced, so it can be concluded that customers are satisfied.